Geometry of the X-ray source 1H 0707–495 - Szanecki, Michał; Niedźwiecki, Andrzej; Done, Chris; Klepczarek, Łukasz; Lubiński, Piotr; Mizumoto, Misaki (Astronomy and astrophysics., 2020)
Aims. We investigate the constraints on the size and location of the X-ray source in 1H 0707–495 determined from the shape of the relativistically smeared reflection from the accretion disc. Methods. We developed a new code to model an extended X-ray source and we applied this code to all archival XMM observations of 1H 0707–495. Results. In contrast to earlier works we find that the relativistic reflection in this source is not consistent with an extended uniform corona. Instead, we find that the X-ray source must be very compact, at most a gravitational radius in size, and located at most a few gravitational radii from the black-hole horizon. A uniform extended corona produces an emissivity that is similar to a twice-broken power-law, but the inner emissivity is fixed by the source geometry rather than being a free parameter. In 1H0707–495, the reflection from the inner disc is much stronger than expected for a uniformly extended source. Including the effect of ionised absorption from the wind does not change this conclusion, but including scattered emission (and more complex absorption) from the wind can dramatically change the reflection parameters.
EPrint Processing Status: Full text deposited in DRO